2015
DOI: 10.1111/nmo.12575
|View full text |Cite
|
Sign up to set email alerts
|

NextGen nuclear DNA sequencing in cyclic vomiting syndrome reveals a significant association with the stress‐induced calcium channel (RYR2)

Abstract: We propose a mechanism in which RYR2 sequence variants result in aberrant stress-induced calcium release into the mitochondria of autonomic neurons, resulting in an increased risk to develop autonomic/functional disease such as CVS, and related conditions such as migraine and gut dysmotility. This model incorporates the existing hypotheses regarding CVS pathogenesis into a cohesive mechanism, and might have treatment implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
(40 reference statements)
0
19
0
2
Order By: Relevance
“…We did not address underlying pathophysiological mechanisms, another poorly studied area in CVS, although there have been a number of potential theories hypothesized previously. These include activation of the corticotrophin‐releasing factor signaling system, abnormal gastric motility, mitochondrial DNA mutations, and other genetic factors including variants in the RYR2 gene, which is involved in stress‐induced calcium channels in autonomic neurons, and polymorphisms in genes encoding endogenous cannabinoid and opioid receptors . In addition, we did not evaluate the subsequent management of these patients, an issue that has been highlighted in the literature as problematic for gastroenterologists, although we have reported data from our center regarding the treatment of CVS previously …”
Section: Discussionmentioning
confidence: 99%
“…We did not address underlying pathophysiological mechanisms, another poorly studied area in CVS, although there have been a number of potential theories hypothesized previously. These include activation of the corticotrophin‐releasing factor signaling system, abnormal gastric motility, mitochondrial DNA mutations, and other genetic factors including variants in the RYR2 gene, which is involved in stress‐induced calcium channels in autonomic neurons, and polymorphisms in genes encoding endogenous cannabinoid and opioid receptors . In addition, we did not evaluate the subsequent management of these patients, an issue that has been highlighted in the literature as problematic for gastroenterologists, although we have reported data from our center regarding the treatment of CVS previously …”
Section: Discussionmentioning
confidence: 99%
“…Inborn errors of metabolism, including fatty acid oxidation disorders and urea cycle defects, have been associated with pediatric CVS . Recent studies found that ion channel polymorphisms (RYR2, SCN4A) that impact cellular stress responses may be associated with CVS . The synergic roles of nuclear DNA mutations (identified by NextGen sequencing) that impact the function of ion channels, axonal transport (KIF1B), or energy production (TRAP1) have been investigated in children with CVS .…”
Section: Pathophysiology and Comorbid Conditionsmentioning
confidence: 99%
“…In addition to acquiring new information from validated survey instruments, it will be useful to adopt a standardized panel of biomarkers from patient specimens to gain insight into CVS pathophysiology. Studies in small cohorts employing blood, urine, and saliva samples to quantify neurohumoral and metabolic functions and genetic profiles of mitochondrial DNA and ion channel distributions, and functional MRI imaging methodologies to discern altered CNS signaling have identified factors which may be of importance in some CVS subsets . Broad‐based application of biomarker panels including these and other testing across multiple centers in diverse CVS patient populations will delineate the relevance of these and other parameters in modifying the clinical presentation of this disorder.…”
Section: Future Research Directions In Cvsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no association was demonstrated in adult-onset CVS,37 39 suggesting that the two are genetically distinct. More recently, next generation sequencing has implicated variants in the RYR2 gene, which is involved in stress-induced calcium channels in autonomic neurons, in the pathophysiology of CVS,40 although the targeted approach used by the investigators means that other potential genetic markers of CVS were not analysed.…”
Section: Aetiology and Pathophysiologymentioning
confidence: 99%